PERLINDUNGAN HUKUM TERHADAP PIHAK YANG BERHAK ATAS TANAH DALAM HAL GANTI RUGI BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - MEILYA NORMAWATY SIMANJUNTAK (PREMISE LAW JURNAL, 2015)
Land acquisition for constructing public facility arouses problem in its practice, in which dispute in land acquisition by the government is increasing. Coercion from various parties such as the government that set the compensation uniterally, the land real owner who asks for unreasonable price, and the existence of consignment institution or the bailment of the compensation in the District Court when the real land owner does not agree on the amount of the compensation will bring about the right and the interest of the real land owner does get legal protection. The problems of the research were as follows: how to avoid conflict in implementing land acquisition for public facility, how about the existence of consignment institution in land acquisition for public acquisition, and how about legal protection for the real land owner, based on Law No. 12/2012 on Land acquisition for public facility. The result of the research showed that, in order to avoid conflict in land acquisition for public facility was by putting forward the principle and the provision of materials in land acquisition and transparency in the procedures of land acquisition, and appropriate and righteous compensation for the real land owner. The consignment which was caused by the disagreement on compensation could not be done because it was government arbitrary action toward the people. Legal protection for the real land owner, especially the compensation, should be based on the principle of justice and feasibility by considering the guarantee for compensation both physically and non-physically so that the consignment which was caused by the disagreement was automatically not needed anymore. Keywords: Land Acquisition, Public Facility, Consignment, Land Compensation